A chromosomally encoded virulence factor protects the Lyme disease pathogen against host-adaptive immunity. - Xiuli Yang; Adam S Coleman; Juan Anguita; Utpal Pal (PLoS Pathogens, 2009)
Borrelia burgdorferi, the bacterial pathogen of Lyme borreliosis, differentially expresses select genes in vivo, likely contributing to microbial persistence and disease. Expression analysis of spirochete genes encoding potential membrane proteins showed that surface-located membrane protein 1 (lmp1) transcripts were expressed at high levels in the infected murine heart, especially during early stages of infection. Mice and humans with diagnosed Lyme borreliosis also developed antibodies against Lmp1. Deletion of lmp1 severely impaired the pathogen's ability to persist in diverse murine tissues including the heart, and to induce disease, which was restored upon chromosomal complementation of the mutant with the lmp1 gene. Lmp1 performs an immune-related rather than a metabolic function, as its deletion did not affect microbial persistence in immunodeficient mice, but significantly decreased spirochete resistance to the borreliacidal effects of anti-B. burgdorferi sera in a complement-independent manner. These data demonstrate the existence of a virulence factor that helps the pathogen evade host-acquired immune defense and establish persistent infection in mammals.